THE PUBLIC HEALTH IMPLICATION OF PATIENT’S RIGHT ABUSE BY HEALTH PROFESSIONALS IN PLATEAU SPECIALIST HOSPITAL, JOS - Emmanuel Mahanan Josiah (International Studies Journal)
Over the years studies indicates that health sectors in both developed and developing nations are vulnerable to patient right abuse by health professionals. This paper discusses the character and scope of patient right abuse by health professionals in Plateau Specialist Hospital, Jos. It suggests that due to the political economy of health,health-seeking behaviours is affected and as such affects the quality of healthcare delivery in the nation. The study further asserts that human rights law can play an important role in enhancing the transparency and integrity of health systems. Based on the existing human rights framework, some tools are provided and examples are given of how this can be done. Furthermore, this study argued that some of such abuses could lead to corrupt acts, as identified under international law. Finally, the study concluded that there are clear links between such corrupt acts and human rights law, and that some of such acts can be identified as concrete human rights violations.